The tired teacher (Journal of Parents and Teachers, 2025)
The article discusses the issues surrounding teacher dissatisfaction and the impact it has on students. It is true that this discomfort can be due to fatigue, personal problems, confusion, routines, and a long list of factors that lead to burnout. Additionally, a series of solutions are mentioned to address these challenges.
Keywords: fatigue; teachers; influence; disconfort